Diagnosis of mycoplasmosis in chicks by pathological and real time-pcr methods - Mehmet Tuzcu; Murat Özmen; S. Reyhan Karakoç; Nevin Tuzcu; Atila Yoldaş (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this study was to investigate the suitability of the Real Time-PCR in the diagnosis of mycoplasmosis and to determine the pathologic findings in lungs, air sacs, trachea, hearth, liver and kidney tissues. Materials and Methods: Conjunctiva and tracheal swab samples were taken from broiler chicks with respiratory disease complaints from 3 different breeders were used. Ten chicks from three separate flock in each breeders were collected. Trachea, air sac, lung, liver, kidney, and heart samples were also collected from the same chicks after necropsy in order to perform pathological, microbiological and Real Time-PCR analyses. Results: Clinically, nasal and conjunctival discharge and wheezing were observed. Macroscopic examination illustrated gross catarrhal exudation in trachea and bronchus. In microscopically, hyperplasia in trachea and bronchus epithelia, mucus producing cells and mononuclear cellular infiltration in lamina propria were observed. Mycoplasma spp. were successfully isolated in the tracheal tissue of 8 broiler chicks. M. gallisepticum specific nucleic acid was amplified from tissue and swab samples of 22 broiler chicks by RT-PCR. Conclusion: RT-PCR seems to be an alternative method when microbiological analyses are laborious or fails in diagnosis of mycoplasmosis.